Uji Aktivitas Isolat Actinomycetes Dari Sampel Pasir Gunung Slamet Terhadap Bakteri Escherichia coli Dan Bacillus subtilis - Utami, Mifta Rizki; , Rima Munawaroh, M.Sc., Apt (2016)
Bacterial resistance to antibacterial drugs, is one serious problem to public health. Based on these problems, it is very important to search for new antibacterial compounds mainly from microorganisms. Actinomycetes are microorganisms which have a high potential as a producer of bioactive compounds including antibacterial compounds. Soil is the habitat of Actinomycetes. The purpose of this study was to determine the number of the isolate of Actinomycetes, the potential of antibacterial produced by Actinomycetes of sand from Mount Slamet on the growth of Escherichia coli and Bacillus subtilis, and to find out the classification of the antibacterial compounds. The isolation of Actinomycetes of the sand from Mount Slamet was done by taking some samples of sand at 5 points of location, pre-treatment of sample sand, the estimation of sample sand was done by using dilution rate of 〖10〗^(-1) to 〖10〗^(-3), isolation on selective media. The media used are Starch casein agar, Starch casein broth, Bennet agar, Queker oatmel agar. The identification of Actinomycetes isolates were done using coloring groups and Gram staining. The antibacterial activity was tested by using agar block methods. Thin Layer Chromatography used silica gel GF254 as stationary phase and n-hexane: ethyl acetate (2:3) as mobile phase. The bioautografi test was done by using the contact bioautography method. The isolation of Actinomycetes of Mount Slamet sample sand obtained 5 isolates of Actinomycetes coded A4, A6, A8, A10, A10b. The Actinomycetes isolate of code A10 has indicated to be able to inhibit the growth of Escherichia coli with diameter of inhibitory zone of 18 mm and Bacillus subtilis with diameter of inhibitory zone of 26 mm. The result of Thin Layer Chromatography and bioautography test indicated that compound having antibacterial activity was of Rf value of 0.97 on Escherichia coli and Bacillus subtilis, are classified as the compounds of terpenoids and propylpropanoids.